Adverse events of cryopreserved hematopoietic stem cell infusions in adults: a single‐center observational study. Issue 6 (16th March 2017) - Otrock, Zaher K.; Sempek, Diane S.; Carey, Sherry; Grossman, Brenda J.
Abstract : BACKGROUND: Autologous hematopoietic stem cell (HSC) transplantation has been used for almost three decades for the management of malignant hematologic diseases and some solid tumors. Dimethyl sulfoxide (DMSO) is used as a cryoprotective agent for hematopoietic progenitor cells (HPCs) collected by apheresis (HPC‐A). We evaluated the factors contributing to the occurrence of adverse events (AEs) of cryopreserved HPC‐A infusion. STUDY DESIGN AND METHODS: Between January 2009 and June 2014, a total of 1269 (1191 patients) consecutive HPC‐A infusions were given to adult patients undergoing autologous HSC transplantation at Barnes‐Jewish Hospital. Only infusions on the first day of transplant were included in the analysis. RESULTS: AEs were reported in 480 (37.8%) infusions. The most common AEs were facial flushing in 189 (39.4%) infusions, nausea and/or vomiting in 183 (38.1%) infusions, hypoxia requiring oxygen in 139 (29%) infusions, and chest tightness in 80 (16.7%) infusions. Multivariate analysis using logistic regression showed that female sex (odds ratio [OR], 1.78; 95% confidence interval [CI], 1.40‐2.26; p < 0.0001), diagnosis other than multiple myeloma (OR, 1.44; 95% CI, 1.12‐1.84; p = 0.004), larger volume of infusion per body weight (OR, 1.66; 95% CI, 1.29‐2.15; p < 0.0001), and number of granulocytes infused per body weight (OR, 1.30; 95% CI, 1.01‐1.67; p = 0.042) were significant predictors of occurrence of AEs during infusion. CONCLUSION: AEs due to HPC‐A infusion occurred in more than one‐third of patients. Interventions need to be instituted to reduce AEs and thus improve the safety of HPC‐A infusion. Many of these toxicities can be attributed to DMSO, and this is reflected in the volume of infusion. It might be warranted to consider implementing DMSO‐reducing protocols before infusion.